2012
DOI: 10.3390/ani2010068
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Animal Research Ethics Committee Membership at American Institutions

Abstract: Simple SummaryThis study analyzed the membership of animal experimentation oversight committees at leading U.S. research institutions. We found the leadership and general membership of these committees to be dominated by animal researchers and the remainder of the committees to be largely comprised of other institutional representatives. These arrangements may contribute to previously-documented committee biases in favor of approving animal experiments and dilute input from the few members representing animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…Committees and their leadership are comprised of a preponderance of animal researchers, and other members who are affiliated with each institution; some of whom also work in animal laboratories. The study concluded that this composition leads to bias in favour of approving animal experiments and reduce the overall objectivity and effectiveness of the oversight system [ 10 ].…”
Section: “Assessment Studies” In the Literaturementioning
confidence: 99%
“…Committees and their leadership are comprised of a preponderance of animal researchers, and other members who are affiliated with each institution; some of whom also work in animal laboratories. The study concluded that this composition leads to bias in favour of approving animal experiments and reduce the overall objectivity and effectiveness of the oversight system [ 10 ].…”
Section: “Assessment Studies” In the Literaturementioning
confidence: 99%
“…Ninety-three percent of IACUC chairpersons were animal researchers. 6 It is not unduly cynical for animal welfare advocates to wonder if an animal-use committee system in which 82% of members and 93% of chairpersons have vested interests in continuing animal research might be subject to an approval bias. The most comprehensive analysis of IACUC reviews found 98% approval rates for in-house research protocols, but that when the same protocols were evaluated by blinded IACUCs from other institutions, 61% were judged as 'not very understandable' or 'not understandable at all', as having poor research designs and procedures, or as justifying the type and number of animals in a way that was 'not very convincing' or 'not convincing at all'.…”
Section: Iacuc Membership Compositions and Protocol Approval Ratesmentioning
confidence: 99%
“…7 Evidence that IACUCs often approve protocols which do not meet federal standards can also be found in Federal audits, government surveys of US Department of Agriculture laboratory inspectors, and USDA reports. 6 The predominance of animal researchers, and the institutional veterinarians who support them on IACUCs, may also explain why IACUCs evolved into exclusively technical or advisory committees rather than ethics committees. The great majority of IACUC members have, through their career choices, made clear their allegiance to animal experimentation, and for them the ethical conclusion that the ends justify the means is self-evident.…”
Section: Iacuc Membership Compositions and Protocol Approval Ratesmentioning
confidence: 99%
“…Plous and Herzog [ 25 ] discussed how this results in an “ethical monoculture” that is likely to impair the ethical committees’ ability to meet public concern for research animal welfare. Another consequence is that the AECs, in practice, perform a technical or advisory role rather than actually making ethical judgments [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Varga [ 24 ] argues that it is valid to compose committees with members who represent different backgrounds and perspectives, as ethical issues are complex and society holds a diversity of views. Hansen, et al [ 32 ] argues that because AECs are the only mechanism in place for addressing the ethics of animal research, it is vital that they consider major ethical issues to a greater extent than is done today. Therefore their composition also needs to reflect a greater ethical diversity than is currently the case in many countries [ 32 ] (Sweden is an exemption here).…”
Section: Introductionmentioning
confidence: 99%